ON SOLVABILITY OF A CLASS OF NONLINEAR INTEGRAL EQUATIONS WITH HAMMERSTEIN TYPE NONCOMPACT OPERATOR IN THE SPACE L_1(R^+) - Khachatryan, Kh.A.; Sardaryan, T.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
In the paper a class of nonlinear integral equations on the positive semi axis with noncompact Hammerstein type operator is studied. The existence of nontrivial, nonnegative, integrable and bounded on R^+ solution is proved. Some specific examples of these equations representing independent interest are given.